Prevalence and determinants of pentavalent booster immunization in children aged three to five years in Denpasar, Bali - Ni Rai Sintarini; Komang Ayu Kartika Sari; I Gusti Agung Trisna Windiani; Anak Agung Sagung Sawitri (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Pentavalent booster immunization coverage in Denpasar City is reported to be relatively low. This study aims to determine the prevalence and determinants of pentavalent immunization uptake. Methods: A cross-sectional study was conducted in one banjar (hamlet) which was selected purposively in the work area of Public Health Centre (PHC) I West Denpasar, Bali Province. Banjar was selected with consideration of the diversity of local residents and migrants. All mothers who had children aged 3-5 years (138 people) in the banjar were chosen as respondents. Interviews were conducted in each respondent's house with variables included age, education, employment, parity, region of origin, knowledge on immunization, perception of susceptibility to and severity of disease, perceptions of benefits and barriers to immunization, sources of information, family support and acceptance of immunization. Data analysis was performed with poisson regression to determine the determinants of pentavalent booster immunization. Results: The majority of respondents were aged <30 years, high school education or above, unemployed, had 1-2 children and were from Bali. The proportion of respondents who reported that their children had been given pentavalent immunization in children aged three to five years was found to be 78.3%. Immunization prevalence was found to be higher in the population that originated from Bali (82.1%). Determinants of pentavalent immunization are perceptions of benefits (APR=4.78; 95%CI: 1.35-16.96) and more sources of information (APR=1.21; 95%CI: 1.04-1.41). Conclusion: The prevalence of pentavalent booster immunization is found to be lower than the average prevalence of the Bali Province but higher than the reported coverage of Denpasar City. The determinants of immunization acceptance was perception of high benefits and more sources of information. Information dissemination on the benefits of pentavalent booster immunization in children needs to be enhanced through health workers and various media to increase the coverage of pentavalent immunization.